Pulmonary emphysema in cystic fibrosis detected by densitometry on chest multidetector computed tomography - Wielpütz, Mark Oliver; Weinheimer, Oliver; Eichinger, Monika; Wiebel, Matthias; Biederer, Jürgen; Kauczor, Hans-Ulrich; Heußel, Claus Peter; Mall, Marcus A.; Puderbach, Michael (PLOS ONE, 2013)
Background: Histopathological studies on lung specimens from patients with cystic fibrosis (CF) and recent results from a mouse model indicate that emphysema may contribute to CF lung disease. However, little is known about the relevance of emphysema in patients with CF. In the present study, we used computationally generated density masks based on multidetector computed tomography (MDCT) of the chest for non-invasive characterization and quantification of emphysema in CF. Methods: Volumetric MDCT scans were acquired in parallel to pulmonary function testing in 41 patients with CF (median age 20.1 years; range 7-66 years) and 21 non-CF controls (median age 30.4 years; range 4-68 years), and subjected to dedicated software. The lung was segmented, low attenuation volumes below a threshold of -950 Hounsfield units were assigned to emphysema volume (EV), and the emphysema index was computed (EI). Results were correlated with forced expiratory volume in 1 s percent predicted (FEV1%), residual volume (RV), and RV/total lung capacity (RV/TLC). Results: We show that EV was increased in CF (457±530 ml) compared to non-CF controls (78±90 ml) (P<0.01). EI was also increased in CF (7.7±7.5%) compared to the control group (1.2±1.4%) (P<0.05). EI correlated inversely with FEV1% (rs=-0.66), and directly with RV (rs=0.69) and RV/TLC (rs=0.47) in patients with CF (P<0.007), but not in non-CF controls. Emphysema in CF was detected from early adolescence (~13 years) and increased with age (rs=0.67, P<0.001). Conclusions: Our results indicate that early onset emphysema detected by densitometry on chest MDCT is a characteristic pathology that contributes to airflow limitation and may serve as a novel endpoint for monitoring lung disease in CF.